Influence of Preparation on Plasticity of some Aluming-Silicates (Journal of Science and Technology, 2016)
The basis of good quality ceramic product development lies in the nature and the preparation of the clays selected and their relative plasticity attributes in forming processes. In this paper, the effects of various pre-treatments such as filter pressing, ageing for one month and ageing for six months on the plasticity of clays have been studied with the compression plastometer. Experimental results have been obtained with the compression plastometer for (a) filter pressed clay (b) unprocessed clay (c) aged clay for one month (d) and ageing for six months called (further ageing period). Results indicate that the compression plastometer is sensitive to particle packing density and that processed filter pressed clay has lower plasticity index than unprocessed clay as measured by the compression plastometer.